Piercing the veil within corporate groups – A comparative overview of Finnish and other European approaches to invoking parent liability - Rantanen, Lauri (fi=Turun yliopisto|en=University of Turku|, 2016)
The topic of this thesis is corporate veil piercing, a judicially developed doctrine according to which unlimited personal liability may be involuntarily thrust upon a shareholder in spite of the widely accepted principle of shareholders’ limited liability for the corporation’s obligations. The objective of this study is to examine the constituent elements of this unlegislated doctrine in four jurisdictions: Finland, Sweden, Germany, and the United Kingdom. The main focus is on corporate group subsidiarisation, i.e. deciphering the relevant factors and their correlation that allow courts to disregard the corporate form of a subsidiary and impose liability on the parent company. Veil piercing case law, relevant discourses in legal literature, and preparatory legislative materials serve as the main reference sources. The research method is thus primarily doctrinal and comparative, but owing to the fundamental significance of limited liability as the cornerstone of today’s economy aspects of law and economics are also included to some extent. The main finding of the comparative analysis is that veil piercing has remained a highly sporadic remedy to constrain value-reducing and socially undesirable forms of opportunism among corporate enterprise constituencies. In addition to high degree of control over a subsidiary, courts require demonstration of non-independence in terms of management and the underlying business interests of the company. The most controversial factor in the assessment is the culpability or disloyalty behind the corporate structure. Conduct amounting to abuse of legal personality seems to be required. It appears that the doctrine might not be capable of capturing the various arrangements corporate groups undertake to encapsulate the business risk in one or more selected companies, ultimately leaving third parties to carry the burden of loss. Despite its unpredictability and other shortcomings, veil piercing can nevertheless offer a flexible equitable remedy when other legal means are not available.